All the Greys on Greene Street - Tucker, Laura, 1973- (Puffin Books, 2020)
In Soho in 1981, twelve-year-old Olympia--an artist--loves her life with her dad and his business partner, Apollo, especially when they restore antique paintings, and with her mother, who makes intricate sculptures in one corner of their loft. This leaves Olympia time to roam New York with Richard and Alex, her best friends, drawing everything she loves. Then, "Ollie's" dad disappears, leaving only a cryptic note with instructions to destroy it and warnings about Apollo, who is hiding something. When she cannot wake her mother up, Olympia realizes her life will never be the same.